Humanistic pedagogic as an orienting point in the realization of student’s moral and spiritual personality features - Beisembayeva, A.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
This article is devoted humanistic pedagogy as a guideline for the fulfillment of spiritual - moral development of students. Humanistic pedagogy puts a person, his creative skills. The teacher’s role is to help him in choosing the basic life guides, solving life conflicts, revealing and realizing internal mental and intellectual resources. The author singles out the moral criteria, value-appraisal orientation, formation of teaching positive motives, actions of national self-awareness, citizenship, patriotism, diligence, moral environment creation in society and a higher institution, identifying and preventing conflict situations, teacher's readiness for moral education of students both in the personal and professional dimension, mutual cooperation in the moral education of youths. In this article the author further shows moral norms, rules and requirements that form the basis of human life and behavior, details the content of spiritual and moral upbringing, indicates its versatility. The scientists’ research in the field of education and upbringing based on humanistic principles, contributing to the creation of a social and psychological atmosphere of mutual trust, mutual cooperation, and actualizing the positive motivational resources of learning are analyzed.
Гуманистік педагогика студенттің жеке тұлғалық рухани-адамгершілік қасиеттерін іске асырудағы бағыт-бағдар ретінде
Гуманистическая педагогика как ориентир в реализации духовно-нравственных качеств личности студента
Keywords: humanism; humanistic pedagogic; spirituality; morality; personality; creative powers; personal qualities